KEBIJAKAN RESTRUKTURISASI ORGANISASI PEMERINTAH DAERAH (STUDI PADA SEKRETARIAT DAERAH KOTA TIDORE KEPULAUAN) - Kasim, Abjan (Jurnal Akrab Juara, 2019)
Policy of local government organization Restructuring as part of effort of reform administration have been done by local government of Tidore city Archipelago specifying By Law of Number 20 in 2006 about Change for By Law of Number 5 in 2005 About Organization and Administration at Secretariat of Tidore city Archipelago and Secretariat of parliament of Tidore city Archipelago.The Method used in this research is descriptive method qualitative as a mean to study, analyzing and giving meaning to policy of organization restructuring of local government in Secretariat Area of Tidore City Archipelago.The theory of Policy public used relate at view of Carl Friedrich and James E. Anderson. While theory of organization restructuring relate at view Mintzberg.Base on the result of research expression that local Government Tidore city Archipelago in practice the government management interpret organization restructuring is equal to addition of organization chart which there have. The mentioned happened because organization restructuring of Secretariat Area of Tidore City Archipelago do not only have base to requirement to reach organizational mission and vision, however is oftentimes happened by the existence intervence various importance from all perpetrator and also stakeholders of area institute, bearing organization peripheral of more area have the character of compromises, so that the organization become less be effective and efficient if is it evaluated from organization principles.